The Effect of Various Vegetable Oils on The Physical - Chemical Properties and Total Plate Count in Making Mayonnaise - Sudjatinah Sudjatinah (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2021)
Mayonnaise is an oil emulsion product in water (o/w). The main component of mayonnaise is fat, or oil derived from vegetable oil. Fat or oil is very influential on the physical, chemical, and characteristics of mayonnaise because of the fatty acid content. The purpose of this study was to determine the effect of differences in the use of vegetable oil in making mayonnaise on physical, chemical, TPC, and antioxidant properties. This research was conducted experimentally, using a randomized block design consisting of 4 treatments, which were palm oil (P1), coconut oil (P2), corn oil (P3), and sunflower oil (P4) with 6 replications, while the observed variables were viscosity, water content, fat content, protein content, antioxidant content, and TPC. The results showed that various types of vegetable oil had a significant effect (p <0.05) on physical properties: viscosity: P1 571.68 cP; P2 676.17 cP; P3 486.14; P4 552.81 cP. Water content P1 16.90%; P2 16.86%, P3 2067%, P4 17.47%, P1 Fat Content 88.96%, P2 75.22%, P3 72.74%, P4 63.97%, P1 Protein Content 1.89%, P2 1.98%, P3 1.83%, P4 1.61%. Antioxidant Content: P1 35.67 ppm P2 28.00 ppm P3 25.00 ppm P4 20.33 ppm, TPC: P1 24.76 CFU/g P2 22.84 CFU/g P3 21.63 CFU/g P4 21.04 CFU/g. The conclusion of this study shows that various types of vegetables have a significant effect (p <0.05) on physical properties (viscosity), chemistry, and TPC of mayonnaise. Coconut oil / VCO (P2) produces mayonnaise with the best moisture content, viscosity, and protein content. Sunflower seed oil (P4) produces mayonnaise with the lowest fat content and TPC, while corn oil (P3) and sunflower seed oil, (P4) produce mayonnaise with almost the same TPC levels. Palm Oil (P1) Produces mayonnaise with the highest Antioxidants.